Electron acceleration in dense plasmas heated by a picosecond relativistic laser. (4th July 2019) - Iwata, N.; Sentoku, Y.; Sano, T.; Mima, K.
Abstract: Laser lights with relativistic intensities and pulse lengths exceeding the picosecond (ps) have been recently made available. Laser–plasma interactions with such a parameter regime belong to the mesoscale between kinetic and fluid regimes, and thus theories developed for sub-ps laser–plasma interactions are not straightforwardly applicable to those for the multi-ps regime. We here study the generation of high-energy electrons in ps relativistic laser–foil interactions by using the particle-in-cell (PIC) simulation. We show that the dynamics of the laser hole boring, which stops during over-ps laser irradiation, is a key to generate the high energy electrons. An energy distribution with a high-energy tail cannot be fitted by a single Maxwellian function, and is likely to be a nonthermal distribution through a stochastic interaction via the recirculation of electrons in the expanding foil plasma. The present study of superthermal electron generation can be a basis for ps laser applications such as fast ignition-based laser fusion, laser ion acceleration, and short-pulse x-ray generation.